2016
DOI: 10.1039/c5tc04433b
|View full text |Cite
|
Sign up to set email alerts
|

Blue upconversion emission of Cu2+ ions sensitized by Yb3+-trimers in CaF2

Abstract: Under 978 nm near-infrared (NIR) excitation, blue upconversion (UC) emissions from CaF2:Cu2+,Yb3+ were first observed at ∼420 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…One appears in the 350−510 nm region with a peak centered at 445 nm while another is in the 350−700 nm region with a peak at ∼530 nm. The emission peaked at 445 nm comes from the 3d 8 4s 1 → 3d 9 transition of Cu 2+ ions, which is similar to that reported previously 45 complexes. 46 Previous studies on the perovskite materials have also shown that broad and white emission can derive from STEs that exist in semiconductors with localized carriers and soft lattices.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…One appears in the 350−510 nm region with a peak centered at 445 nm while another is in the 350−700 nm region with a peak at ∼530 nm. The emission peaked at 445 nm comes from the 3d 8 4s 1 → 3d 9 transition of Cu 2+ ions, which is similar to that reported previously 45 complexes. 46 Previous studies on the perovskite materials have also shown that broad and white emission can derive from STEs that exist in semiconductors with localized carriers and soft lattices.…”
supporting
confidence: 88%
“…One appears in the 350–510 nm region with a peak centered at 445 nm while another is in the 350–700 nm region with a peak at ∼530 nm. The emission peaked at 445 nm comes from the 3d 8 4s 1 → 3d 9 transition of Cu 2+ ions, which is similar to that reported previously while the emission peaked at 530 nm may reflect the transition from CBM to the different defect states and/or surface related states of Cs 2 AgInCl 6 . The overall relaxation pathways of fluorescence emission of undoped Cs 2 AgInCl 6 and Cu 2+ -doped Cs 2 AgInCl 6 sample are illustrated in Figure c.…”
supporting
confidence: 88%
“…In addition, the weaker Urbach tails in the CsPb 1– x Cu x Br 3 QD absorption spectra reveal that doping Cu 2+ can indeed contribute to better crystallinity of perovskite QDs and thus a sharp absorption edge. , The PL spectra reveal that the emission peak of CsPb 1– x Cu x Br 3 QDs experiences a blue shift from 517 to 499 nm (Figure b) with increasing x value. Notably, an additional PL peak of CsPb 0.77 Cu 0.23 Br 3 QDs at 430 nm can be observed in Figure b, which may be due to emission of Cu 2+ in the host at a high doping level . Generally, the blue-shifted optical spectra can be attributed to contraction of the host perovskite, leading to a stronger interaction between Pb and Br orbitals.…”
mentioning
confidence: 93%
“…This may be due to the emission of Ni 2+ in the host at a high doping level. [ 35,36 ] The PL intensity increased gradually with increasing substituted concentration of Ni 2+ ions. However, the others PL peaks (Ni/Pb = 3.75, 5) decreased.…”
Section: Resultsmentioning
confidence: 99%